PO 3 - SEIZURES DURING LABOUR – ECLAMPSIA IS NOT THE ONLY OPTION - Filipa Sales1; Cláudia Pereira2; Paula Rebelo2; Ana Nogueira2; Mariana Cunha2; Teresa Rebelo2 (Journal of the Portuguese Society of Anesthesiology, 2023)
.